2014
DOI: 10.1016/j.annepidem.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous vegetables, glutathione S-transferase polymorphisms, and the risk of colorectal cancer among Chinese men

Abstract: Purpose To assess the associations between cruciferous vegetable (CV) intake, GST gene polymorphisms and colorectal cancer (CRC) in a population of Chinese men. Methods Using incidence density sampling, CRC cases (N = 340) diagnosed prior to December 31, 2010 within the Shanghai Men’s Health Study were matched to non-cases (N = 673). CV intake was assessed from a food frequency questionnaire and by isothiocyanate (ITC) levels from spot urine samples. GSTM1 and GSTT1 were categorized as null (0 copies) versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…There were 25 duplicates (figure 1); 214 papers were excluded because 28 were conference posters, 54 were reviews, 84 regarded other subjects, 30 were animal, in vitro or laboratory technique studies, and 18 evaluated blood/serum/plasma or other tissues. Examination of the remaining 50 papers in the second stage of the PRISMA flow chart led to the exclusion of 31studies for the following reasons: 5 were reviews 1,19,42-44, one assessed animals 45, 5 involved laboratory technique validation 21, 46-49, one was a molecular biology study 50, 4 were survival analysis studies 51-54, 7 assessed the impact of dietary habits 57-61, 5 did not examine urine 62-66, one reported aggregate data for CRC, gastric cancer and pancreatic cancer 67, and finally 2 did not match the inclusion criteria 68,69.…”
Section: Resultsmentioning
confidence: 99%
“…There were 25 duplicates (figure 1); 214 papers were excluded because 28 were conference posters, 54 were reviews, 84 regarded other subjects, 30 were animal, in vitro or laboratory technique studies, and 18 evaluated blood/serum/plasma or other tissues. Examination of the remaining 50 papers in the second stage of the PRISMA flow chart led to the exclusion of 31studies for the following reasons: 5 were reviews 1,19,42-44, one assessed animals 45, 5 involved laboratory technique validation 21, 46-49, one was a molecular biology study 50, 4 were survival analysis studies 51-54, 7 assessed the impact of dietary habits 57-61, 5 did not examine urine 62-66, one reported aggregate data for CRC, gastric cancer and pancreatic cancer 67, and finally 2 did not match the inclusion criteria 68,69.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Cdc20 upregulation was associated with aggressive tumor progression and poor prognosis in gastric cancer [5] and primary non-small cell lung cancer [8] . Surprisingly, an increased expression of Cdc20 was detected in metastatic liver tissue in patients with colorectal cancer [6] . In addition, overexpression of Cdc20 was measured with a high grade in bladder, cervical, colon, endometrial, gastric, liver, ovarian, prostate, and renal carcinomas [9] .…”
Section: Implications Of All the Available Evidencementioning
confidence: 95%
“…diseases or predispose normal cells to become malignant [2,3] . Results from TCGA (The Cancer Genome Atlas) and pathological analysis have revealed a strong connection between aberrant upregulation of Cdc20 and various types of cancers [5][6][7][8] . For instance, severe accumulation of Cdc20 was detected in breast cancer cells and colon cancer cells compared to normal epithelial cells and adjacent normal tissues in cancer patient specimens.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…It has been suggested that homozygotic deletion of the functional alleles of GSTM1 increases the risk of colorectal cancer, although many studies conducted in several populations have produced debatable outcomes. Several research groups have reported a remarkable incidence of the GSTM1 null genotype in patients with colorectal cancer (Saeed et al, 2013;Cai et al, 2014;Cong et al, 2014;Ma et al, 2014;Teng et al, 2014;Djansugurova et al, 2015), while others failed to validate this result (Hezova et al, 2012;Kassab et al, 2014;Vogtmann et al, 2014).…”
Section: Introductionmentioning
confidence: 95%